2017
DOI: 10.1160/th17-04-0241
|View full text |Cite
|
Sign up to set email alerts
|

Down Regulation of the Munc18b-syntaxin-11 Complex and β1-tubulin Impairs Secretion and Spreading in Neonatal Platelets

Abstract: Neonatal platelets are hyporeactive and show impaired agonist-induced secretion despite no obvious abnormalities in their granules. Here, we examined, for the first time, the ultrastructure of neonatal and adult platelets following agonist activation. Under resting conditions, neonatal and adult platelets appeared ultrastructurally identical. Following agonist stimulation, however, noticeable degranulation occurred in adult platelets, while granules in neonatal platelets remained clearly visible and apparently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 45 publications
5
33
2
Order By: Relevance
“…Since the centralization of granules is a process that depends on the contraction of the microtubule marginal coil [31,64], and β1-tubulin is its main isoform (up to 90% of total β tubulin in megakaryocytes and platelets), we investigated whether β1-tubulin expression is developmentally regulated. Our findings showed a significant reduction in β1-tubulin mRNA ( TUBB1 ) (~40%) and protein expression levels in neonatal compared to adult platelets (Figure 4A,B with permission) [63]. Neonatal platelets, however, displayed a microtubular ring similar to the present one in adult platelets (Figure 4C,D with permission) [63], suggesting that half the usual amount of β1-tubulin may be sufficient to allow the characteristic discoid shape.…”
Section: Implications Of Tubulin Genetic Variability In Pathologicmentioning
confidence: 72%
See 3 more Smart Citations
“…Since the centralization of granules is a process that depends on the contraction of the microtubule marginal coil [31,64], and β1-tubulin is its main isoform (up to 90% of total β tubulin in megakaryocytes and platelets), we investigated whether β1-tubulin expression is developmentally regulated. Our findings showed a significant reduction in β1-tubulin mRNA ( TUBB1 ) (~40%) and protein expression levels in neonatal compared to adult platelets (Figure 4A,B with permission) [63]. Neonatal platelets, however, displayed a microtubular ring similar to the present one in adult platelets (Figure 4C,D with permission) [63], suggesting that half the usual amount of β1-tubulin may be sufficient to allow the characteristic discoid shape.…”
Section: Implications Of Tubulin Genetic Variability In Pathologicmentioning
confidence: 72%
“…Our findings showed a significant reduction in β1-tubulin mRNA ( TUBB1 ) (~40%) and protein expression levels in neonatal compared to adult platelets (Figure 4A,B with permission) [63]. Neonatal platelets, however, displayed a microtubular ring similar to the present one in adult platelets (Figure 4C,D with permission) [63], suggesting that half the usual amount of β1-tubulin may be sufficient to allow the characteristic discoid shape. Our results are in agreement with those reported for p.Q43P β1-tubulin variant homozygous carriers, whose platelets, despite having half the normal levels of β1-tubulin, mostly displayed a normal marginal band and a discoid shape [63,65].…”
Section: Implications Of Tubulin Genetic Variability In Pathologicmentioning
confidence: 72%
See 2 more Smart Citations
“…Moreover, the level of P-selectin expression was unaffected following immune thrombocytopenia. Notably, while in humans total P-selectin content is similar between adult and neonatal platelets, 39 in mice it has been suggested that P-selectin expression is developmentally regulated. 40 Thus, the marked reduction in P-selectin secretion induced by CRP and rhodocytin in gestational and early neonatal mice platelets that we have observed may be mediated by a combination of reduced activation of their ITAM receptors and by developmental up-regulation of the α-granule protein.…”
Section: Discussionmentioning
confidence: 99%